FAKTOR-FAKTOR PENYEBAB KEMENANGAN PASANGAN SYAMSUAR-ALFEDRI DI KECAMATAN TUALANG DALAM PEMILIHAN KEPALA DAERAH KABUPATEN SIAK TAHUN 2015 - Naufal Pardi; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aimed to describe factors related to the cause of Victory pair Syamsuar-Alfedri in District Tualang in local elections Siak Year 2015. The figure Syamsuar-Alfedri considered a decent figure was boosted primarily in the District Tualang, proven leadership of one period of their own many programs running felt that touch directly to the public.The problem in this research is the causative factors Is Victory pair Syamsuar-Alfedri in District Tualang in Siak regency elections in 2015. The results of this study are Syamsuar-Alfedri the Regent Siak who served one year period ie 2011 to 2016 that is running very well the previous Government, namely intelligence, social relationships, motivation and encouragement of achievement. With his ability, he was able to bring Siak Regency was named the New Autonomous Region (DOB) best in Indonesia, factor underlying improvement in the economy has Syamsuar-Afedri regents victory in District Tualang. Starting from Revenue Per-Capita, tourism and culture, ivestasi, agriculture, plantations, farms, cooperatives, numbers Savings, and the Human Development Index, and Factor support Parties in Siak, especially in the district of Tualang for Syamsuar and Alfedri also merupan wrong one Important factors victory in District Tualang.Keywords: victory, Couples, Regional Head Election